IL-6R (trans-signaling) is a key regulator of reverse cholesterol transport in lipid-laden macrophages - Al-Rashed, Fatema (Clinical immunology (Orlando, Fla.), 2024)
Copyright © 2024 The Authors. Published by Elsevier Inc. All rights reserved.